O papel do controller: um estudo no contexto brasileiro - Calijuri, Monica Sionara Aschpallir (2005)
Controllership has developed a new dimension on companies management. From an impending accounting or explanative character it has evolved to presenting prognostic models, completing simulations of future settings and identifying new business opportunities. During the 50 s, the controller was the person in charge, fundamentally, of preparing financial statements. Throughout recent years, as the companies organizations has increased, it has been created the need of a more adapted system to achieve an effective management, hence, the development of a differentiated function and the controller s shift to new tasks. In sight of changes, the necessity appeared more of deepened studies, enclosing the new profile of controller, especially in the Brazilian context. The objective of this work is contribute to the controllership s studies and to present the role of this new professional on current time. Exploratory research has been used as part of this work s realization, having as instrument the application of questionnaires sent to a determined segment and received by e-mail. The outcome of the research demonstrates the existence of a new controllership profile that demands professionals with a solid academic history, leadership spirit and flexibility to changes